Lithium ion secondary battery
By setting recesses on the surface of the negative electrode active layer and controlling parameters such as particle size and separator strength of the siliceous carbon material, the problem of lithium-ion secondary batteries being easily expanded due to the negative electrode doped silicone material is solved, and the battery cycle life and energy density are improved, while reducing internal resistance.
Patent Information
- Application Number
- CN202510640890.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-16
- Publication Date
- 2025-08-19
AI Technical Summary
Lithium-ion secondary batteries are prone to expansion due to the silicon-doped negative electrode, resulting in short cycle life and large internal resistance of the battery.
The recesses are provided on the surface of the negative electrode active layer, and the average particle size, ash content, width and spacing of the recesses, and tensile strength of the diaphragm are coordinated to ensure that they meet a specific range. Combined with the diaphragm of suitable strength, a stress release space and flow channel are provided to suppress the expansion of the negative electrode sheet and reduce internal resistance.
Effectively suppress the expansion of the negative electrode sheet, improve the cycle life and energy density of lithium-ion secondary batteries, reduce the internal resistance of the battery, and improve electrochemical performance.
Smart Images

Figure CN120511342A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical devices, and in particular to a lithium ion secondary battery. Background Art
[0002] Lithium-ion secondary batteries are common electrochemical energy storage devices with a wide range of applications. The negative electrode is an important component of lithium-ion secondary batteries, affecting the battery's cycle life and other performance. Among them, silicon-doped negative electrodes can increase the battery's energy density. However, due to factors such as the easy expansion of silicon-doped negative electrodes, lithium-ion secondary batteries generally have problems such as short cycle life and high internal resistance, which need to be urgently addressed. Summary of the Invention
[0003] The present invention provides a lithium ion secondary battery to at least solve the problems of the prior art such as short cycle life and large internal resistance of the battery.
[0004] The present invention provides a lithium-ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet, and a separator located between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode active layer, the negative electrode active layer comprises a negative electrode active material, the negative electrode active material comprises a silicon-carbon material, and a concave portion is provided on the surface of the negative electrode active layer; the silicon-carbon material comprises porous carbon and silicon present in the pores of the porous carbon; the ash content a of the negative electrode active layer is 2% to 50%; the average particle size of the silicon-carbon material is 1 to 15 μm; 1≤w2-w1≤6; 0.025≤L / σ≤0.1; 0.18≤S / σ≤1.2; wherein w1 is the width of the negative electrode sheet, measured in mm; w2 is the width of the separator, measured in mm; L is the width of the concave portion, measured in μm; S is the spacing between the concave portions, measured in μm; σ is the tensile strength of the separator, measured in kgf / cm 2 count.
[0005] According to one embodiment of the present invention, 15000≤σ*h≤51000, where the unit of σ is kgf / cm 2 h is the depth of the recess, in μm.
[0006] According to one embodiment of the present invention, 23000≤σ*h≤51000, where the unit of σ is kgf / cm 2 h is the depth of the recess, in μm.
[0007] According to one embodiment of the present invention, the diaphragm includes a base film and a ceramic layer located on at least one side of the base film.
[0008] According to one embodiment of the present invention, 0.00014≤k / S≤0.0005; and / or, 0.15≤A / S≤0.4; and / or, 18≤k*L≤57; and / or, 19000≤A*L≤60000; wherein, k is the porosity of the basement membrane; A is the pore size of the basement membrane, in nm; L is in μm; S is in μm; and / or, the porosity k of the basement membrane is 20% to 60%; and / or, the pore size A of the basement membrane is 50 to 550 nm.
[0009] According to one embodiment of the present invention, the ceramic layer is located on a side of the base film facing the positive electrode sheet.
[0010] According to one embodiment of the present invention, 13000≤L*B≤34000, where L is measured in μm; B is the air permeability of the diaphragm, measured in sec / 100cc; preferably, the air permeability B of the diaphragm is 100-350sec / 100cc.
[0011] According to one embodiment of the present invention, 250≤S / (w2-w1)≤1300, the units of w1 and w2 are mm; the unit of S is μm.
[0012] According to one embodiment of the present invention, 0.027≤L / σ≤0.07.
[0013] According to one embodiment of the present invention, the width L of the recess is 60 to 150 μm; and / or the spacing S of the recess is 800 to 2800 μm; and / or the depth h of the recess is 5 to 30 μm; and / or the tensile strength σ of the diaphragm is 1350 to 3000 kgf / cm 2 .
[0014] According to one embodiment of the present invention, the negative electrode active material includes a carbon-based material and the silicon-carbon material; preferably, the carbon-based material includes at least one of artificial graphite and natural graphite; preferably, the silicon element in the silicon-carbon material accounts for 20wt% to 60wt%.
[0015] The lithium-ion secondary battery provided by the present invention introduces a silicon-carbon material into the negative electrode sheet (i.e., the negative electrode is doped with silicon), which can ensure the high energy density of the negative electrode sheet, while controlling the average particle size of the silicon-carbon material to 1-6 μm and the ash content a of the negative electrode active layer to 2%-50%. In addition, recesses are provided on the surface of the negative electrode active layer, and the spacing S of the recesses, the width L of the recesses, and the tensile strength σ of the diaphragm are coordinated and regulated to satisfy 0.025≤L / σ≤0.1 and 0.18≤S / σ≤1.2. At the same time, the difference between the width of the diaphragm and the width of the negative electrode sheet is controlled within the range of 1-6 mm (i.e., 1≤w2-w1≤6), which can effectively suppress the expansion of the silicon-doped negative electrode, improve the cycle life of the lithium-ion secondary battery, and simultaneously reduce the internal resistance of the battery and improve the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a schematic structural diagram of a negative electrode sheet according to an embodiment of the present invention;
[0017] Figure 2 This is a surface photograph of the negative electrode active layer of Example 1 of the present invention;
[0018] Figure 3 Schematic diagram of the stacked structure of the positive electrode sheet, the separator and the negative electrode sheet in a battery cell according to one embodiment of the present invention;
[0019] Figure 4 This is a schematic diagram of the battery cell structure according to one embodiment of the present invention;
[0020] Figure 5 Schematic diagram of the planar structure of the separator and the negative electrode sheet in one embodiment of the present invention.
[0021] Explanation of reference numerals: 1: negative electrode sheet; 11: negative electrode current collector; 12: negative electrode active layer; 101: first side; 102: second side; 13: recessed portion; 110: first straight portion; 120: first bent portion; 100: negative electrode tab; 2: positive electrode sheet; 21: positive electrode current collector; 22: positive electrode active layer; 200: positive electrode tab; 210: second straight portion; 220: second bent portion; 3: diaphragm; 31: base film; 32: ceramic layer; 33: First coating layer; 34: second coating layer; L: width of the recess; S: distance between two adjacent recesses; h: depth of the recess; S1: distance between the outer edge of the recess closest to the first side of the first coating and the outer edge of the first side of the first coating; S2: distance between the outer edge of the recess closest to the outer edge of the second side of the first coating and the outer edge of the second side of the first coating; x: first direction; y: second direction; z: third direction; w1: width of the negative electrode sheet; w2: width of the separator. DETAILED DESCRIPTION
[0022] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific embodiments listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts are within the scope of protection of the present invention.
[0023] In the present invention, unless otherwise specified, “*” represents a product relationship, that is, “A*B” represents the product of A and B.
[0024] In related technologies, due to factors such as the easy expansion of silicon-doped negative electrodes, lithium-ion secondary batteries generally have problems such as short cycle life and large internal resistance, which need to be solved urgently.
[0025] According to the research of the inventors of this application, after the negative electrode is doped with silicon (i.e., silicon-carbon material is introduced into the negative electrode active layer of the negative electrode sheet), the silicon-carbon material particles are prone to expansion during the battery cycle, which produces a large expansion stress on the negative electrode active layer. The repeated expansion and contraction of the silicon-carbon material particles will cause the relative movement of the negative electrode active material particles in the negative electrode active layer, reducing the adhesion and close contact between the particles, thereby affecting the cycle life and electrochemical performance of the negative electrode sheet, and making the negative electrode sheet prone to expansion and extension during the battery cycle, resulting in problems such as excessive thickness of the battery cell. At the same time, the negative electrode active material particles in the negative electrode sheet are displaced, which increases the polarization of the battery cell and reduces the cycle life of the lithium-ion secondary battery.
[0026] According to further research by the inventors of this application, providing a recess on the surface of the negative electrode active layer (specifically, laser marking can be used to form notches (i.e., recesses) on the surface of the negative electrode active layer) can, to a certain extent, suppress problems such as the expansion of the negative electrode sheet caused by the doping of silicon in the negative electrode. However, the formation of the recess on the surface of the negative electrode sheet will reduce the strength of the negative electrode sheet, making it easy for the negative electrode sheet to expand laterally and longitudinally, and the negative electrode sheet to move relative to the diaphragm and the positive electrode sheet, resulting in an increase in the ion transfer impedance, which in turn leads to an increase in the internal resistance of the battery and deterioration in the electrochemical performance. At the same time, the repeated extension and excessive extension of the negative electrode sheet during the battery charging and discharging process will also increase the fatigue of the battery shell (the outer packaging film shell that encapsulates the battery cell), which can easily cause damage to the shell and affect the service life of the battery.
[0027] In view of this, an embodiment of the present invention provides a lithium ion secondary battery (hereinafter referred to as battery), such as Figures 1 to 4As shown, the battery includes a positive electrode sheet 2, a negative electrode sheet 1, and a separator 3 located between the positive electrode sheet 2 and the negative electrode sheet 1. The negative electrode sheet 1 includes a negative electrode active layer 12, and the negative electrode active layer 12 includes a negative electrode active material (or negative electrode active substance). The negative electrode active material includes a silicon-carbon material. A concave portion 13 is provided on the surface of the negative electrode active layer 12. The silicon-carbon material includes porous carbon and silicon present in the pores of the porous carbon. The ash content a of the negative electrode active layer is 2% to 50%. %; the average particle size D of the silicon-carbon material is 1 to 15 μm; 1≤w2-w1≤6; 0.025≤L / σ≤0.1; 0.18≤S / σ≤1.2; wherein w1 is the width of the negative electrode sheet, measured in mm; w2 is the width of the separator, measured in mm; L is the width of the recess 13, measured in μm; S is the spacing between the recesses 13, measured in μm; σ is the tensile strength of the separator 3, measured in kgf / cm 2 count.
[0028] According to the inventor's research, the ash content a of the negative electrode active layer 12 is related to the content of silicon-carbon material in the negative electrode active layer 12. The larger the ash content a of the negative electrode active layer 12, the more silicon-carbon material there is in the negative electrode active layer 12. When there is more silicon-carbon material, the expansion effect of the negative electrode sheet is relatively greater. At the same time, the larger the particle size of the silicon-carbon material, the greater the force exerted on the diaphragm after expansion. The arrangement of the concave portion 13 on the surface of the negative electrode active layer 12 can provide space for the expansion of the silicon-carbon material to release stress. The larger the width L of the concave portion 13, the more space is provided. The smaller the spacing S of the concave portion 13, the more concave portion 13 is, and the more space is provided. Therefore, when a is 2 % to 50%, and D is 1 to 15 μm, and the width L and spacing S of the recess 13, as well as the tensile strength σ of the diaphragm are coordinated and regulated to satisfy 0.025≤L / σ≤0.1, 0.18≤S / σ≤1.2, and control 1≤w2-w1≤6. In this way, after the silicon-carbon material expands, the recesses with appropriate width and spacing can provide space for releasing stress for the expansion of the silicon-carbon material. At the same time, the recesses can also provide flow channels for the electrolyte, making it easier for the electrolyte to infiltrate the negative electrode sheet. At the same time, the diaphragm adapted thereto can restrain the further expansion of the silicon-carbon material based on its strong tensile strength, and restrain the movement of silicon-carbon particles to prevent them from moving and being punctured by the silicon-carbon material.
[0029] More specifically, by providing a recess 13 on the surface of the negative electrode active layer 12, and cooperatively regulating the average particle size D of the silicon-carbon material, the ash content a of the negative electrode active layer 12, the width L of the recess 13, the spacing S of the recess 13, and the tensile strength σ of the separator 3 to satisfy the above range, in such a battery system, by introducing silicon-carbon material into the negative electrode active layer 12, the energy density of the negative electrode sheet 1 and the battery can be improved. At the same time, the recess 13 provided on the surface of the negative electrode active layer 12 can provide a space for releasing stress for the expansion of the silicon-carbon material, inhibit the expansion of the negative electrode sheet 1 and the resulting problems such as excessive thickness of the battery cell, reduce the cycle expansion rate of the battery, and provide a flow channel for the electrolyte, which is beneficial to the infiltration of the electrolyte and ion transport, and reduces the polarization of the battery. At the same time, with a separator of appropriate strength Membrane 3 can provide a wider tolerable range for the expansion of silicon-carbon materials, and is conducive to binding particles such as silicon-carbon materials in the negative electrode sheet 1, reducing the movement between particles of silicon-carbon materials and other materials in the negative electrode active layer 12, maintaining the relative stability between particles in the negative electrode active layer 12, avoiding the negative electrode sheet 1 from falling off, and poor contact between particles, which leads to obstruction of carrier transmission, and thus leads to high battery impedance and other problems. At the same time, based on the binding effect of the diaphragm 3, the relative movement between the negative electrode sheet 1 and the positive electrode sheet 2 and the diaphragm 3 can be reduced, and the structural stability and other performance of the battery cell formed by the positive electrode sheet 2, the diaphragm 3 and the negative electrode sheet 1 can be improved. The contact between the electrode interfaces can be improved, and the polarization and other problems during the battery operation process can be reduced, thereby improving the cycle life of the battery, reducing the internal resistance of the battery, and reducing the problem of lithium plating at the negative electrode. Therefore, the embodiment of the present invention can take into account the reduction of the battery cycle expansion rate and internal resistance, and reduce the phenomenon of lithium plating at the negative electrode, and improve the energy density and capacity retention rate of the battery.
[0030] For example, L / σ can be 0.025, 0.027, 0.03, 0.035, 0.04, 0.045, 0.05, 0.055, 0.06, 0.065, 0.07, 0.08, 0.09, 0.1, or a range consisting of any two thereof. In some embodiments, 0.027≤L / σ≤0.07 is beneficial for further reducing the cycle expansion rate and DC internal resistance of the battery, inhibiting lithium plating at the negative electrode, and improving the energy density and capacity retention rate of the battery.
[0031] Illustratively, S / σ can be 0.18, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.14, 1.18, 1.2, or a range consisting of any two thereof.
[0032] Illustratively, the ash content a of the negative electrode active layer 12 may be 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or a range consisting of any two thereof.
[0033] For example, the difference between the width w2 of the separator 3 and the width w1 of the negative electrode sheet 1 (ie, w2-w1) may be 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, or a range consisting of any two thereof.
[0034] In the embodiment of the present invention, the ash content a of the negative electrode active layer 12 is related to the content of the silicon-carbon material in the negative electrode active layer 12 (the two are substantially equal), and the ash content a of the negative electrode active layer 12 can be measured by testing methods such as thermogravimetric analysis. The testing process of the ash content a of the negative electrode active layer 12 may specifically include: removing the negative electrode active layer 12 material from the negative electrode sheet 1 (for example, soaking the negative electrode sheet 1 in water to soak the negative electrode active layer 12 material on the negative electrode current collector 11, and then drying the soaked negative electrode active layer 12 material (the negative electrode active layer 12 material after drying is a negative electrode powder)), measuring the mass of the negative electrode active material (negative electrode powder) as m1, and then calcining the negative electrode active layer 12 material in an air atmosphere at 800°C±5°C in a muffle furnace or other equipment for 8h±5min to obtain a calcined product (the remaining material after calcining the negative electrode active layer 12 material), measuring the mass of the calcined product as m2, and then the ash content a of the negative electrode active layer 12 = m2 / m1.
[0035] For example, the average particle size D of the silicon-carbon material may be 1 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, or a range consisting of any two thereof.
[0036] In some embodiments, the particle size D of the silicon-carbon material can be 6 to 15 μm, for example, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm or a range consisting of any two of them, which is beneficial for providing space for the silicon-carbon material to release stress through the recess 13, inhibiting the expansion of the negative electrode sheet 1, reducing the cycle expansion rate of the battery, and at the same time taking into account the improvement of the energy density of the battery. At the same time, the particle size D of the silicon-carbon material is more suitable, which is beneficial for reducing the side reaction between the silicon-carbon material and the electrolyte, thereby further reducing the cycle expansion rate of the battery and improving the cycle life and other performance of the battery.
[0037] Specifically, the silicon-carbon material includes porous carbon and silicon filled in the porous carbon. That is, the silicon-carbon material includes a material in which silicon is filled (including partially filled or completely filled) in pores of the porous carbon.
[0038] In the embodiment of the present invention, the silicon-carbon material is a conventional silicon-carbon negative electrode active material in the art, which can be commercially obtained or prepared by conventional methods in the art. For example, silicon can be deposited on a carbon skeleton (carbon material) by chemical vapor deposition using silane gas to obtain the silicon-carbon material.
[0039] In an embodiment of the present invention, the average particle size D of the silicon-carbon material can be measured by an analytical method such as a scanning electron microscope (SEM) or other electron microscopes, a laser particle size analyzer, etc. In a specific implementation, the average particle size D of the silicon-carbon material can be measured by the following process: using an argon ion milling device to prepare a cross-sectional sample of the negative electrode sheet 1, using an SEM, selecting a backscattering mode, and measuring the particle size D' (i.e., the farthest distance of the cross-sectional profile of the silicon-carbon material particle (i.e., the maximum size of the silicon-carbon material particle)) of the silicon-carbon material particle at a magnification of 1K, measuring the particle size D' of at least 20 silicon-carbon material particles in 5 (or more) different areas of the cross-sectional sample (at least 4 silicon-carbon material particles are tested in each area), and then calculating the average value of the measured particle size D' of at least 20 silicon-carbon material particles, which is the particle size D of the silicon-carbon material.
[0040] In the embodiment of the present invention, the particle size characteristics of materials such as silicon-carbon materials can be controlled by conventional methods in the art, and there is no particular limitation on this.
[0041] like Figure 1 and Figure 2 As shown, the surface of the negative electrode active layer 12 is distributed with multiple (>1) recesses 13, which can be distributed along a first direction x. Two adjacent recesses 13 are separated by the negative electrode active layer 12. The spacing S between the recesses 13 refers to the distance between the two adjacent recesses 13 in the first direction x, where S>0. The width direction of the recess 13 is substantially parallel to the first direction x, and the length direction (extension direction) of the recess 13 is substantially perpendicular to the first direction x.
[0042] Continue to refer Figure 1 and Figure 2 The negative electrode active layer 12 has a first side 101 and a second side 102 opposite to each other in the first direction x. A distance S1 between the concave portion 13 closest to the outer edge of the first side 101 of the negative electrode active layer 12 and the outer edge of the first side 101 of the negative electrode active layer 12 is less than or equal to a spacing S between two adjacent concave portions 13 (S1≤S). A distance S2 between the concave portion 13 closest to the outer edge of the second side 102 of the negative electrode active layer 12 and the outer edge of the second side 102 of the negative electrode active layer 12 is less than or equal to S (S2≤S), so that the concave portions 13 are arranged at a spacing S on the entire surface of the negative electrode active layer 12.
[0043] In some embodiments, the spacing S of the recesses 13 can be 800 to 2800 μm, for example, 800 μm, 1000 μm, 1200 μm, 1500 μm, 1800 μm, 2000 μm, 2300 μm, 2500 μm, 2800 μm or a range consisting of any two of them, which is beneficial for providing space for releasing stress during the expansion of negative electrode materials such as silicon-carbon materials and providing a flow channel for the electrolyte, while taking into account maintaining the high strength and energy density of the negative electrode sheet 1, and can further avoid problems such as powder loss of the negative electrode sheet and obstruction of carrier transmission due to poor contact between particles. At the same time, it is also beneficial to take into account a better interface contact between the negative electrode sheet 1 and the diaphragm 3, thereby reducing the internal resistance of the battery, thereby further taking into account improving the cycle performance of the battery and reducing the battery cycle expansion rate and internal resistance.
[0044] In some embodiments, the width L of the recess 13 can be 60 to 150 μm, for example, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm or a range consisting of any two of them, which is beneficial to the expansion of negative electrode materials such as silicon-carbon materials, provides space for releasing stress, and provides a flow channel for the electrolyte, while taking into account maintaining the high strength and energy density of the negative electrode sheet 1, and further taking into account improving the cycle performance of the battery and reducing the battery cycle expansion rate and internal resistance.
[0045] In some embodiments, the depth h of the recess 13 can be 5 to 30 μm, for example, 5 μm, 10 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 25 μm, 28 μm, 30 μm or a range consisting of any two of them, which is beneficial to the expansion of negative electrode materials such as silicon-carbon materials, provides space for releasing stress, and provides a flow channel for the electrolyte, while taking into account maintaining a high energy density of the negative electrode sheet 1, and further taking into account improving the cycle performance of the battery and reducing the battery cycle expansion rate and internal resistance.
[0046] In an embodiment of the present invention, a laser can be used to create recesses 13 of a preset shape and parameters such as width, length, and spacing on the surface of the negative electrode active layer 12. That is, the recesses 13 on the surface of the negative electrode active layer 12 can be formed by laser etching. In a specific implementation, the laser can be irradiated on the surface of the negative electrode active layer 12 to burn and etch the negative electrode active material and other materials on the surface of the negative electrode active layer 12. In accordance with the movement trajectory of the laser, a groove (i.e., recess 13) is formed. Specifically, parallel linear grooves (i.e., linear grooves) can be formed. The width and depth of the recesses 13 can be adjusted by regulating parameters such as the diameter and power of the laser. These control methods are conventional operations in the art and will not be described in detail.
[0047] After the negative electrode sheet 1 is formed into a recess 13 by laser etching or other methods, the negative electrode active material will be reduced, and the lithium ion diffusion position at the edge of the negative electrode sheet 1 will be reduced (for example, it will be reduced by half compared to the middle position). At the same time, after the recess 13 is formed by laser etching or other methods, the thickness of the edge and middle positions of the negative electrode sheet 1 will be different to a certain extent, and the deintercalation rate of lithium ions will be different. In addition, the active lithium in the electrolyte is likely to produce a tidal effect at the edge of the negative electrode sheet 1, making the negative electrode sheet 1 prone to edge lithium precipitation. By collaboratively controlling the negative electrode The ash content a of the active layer is 2% to 50%, the average particle size of the silicon-carbon material is 1 to 15 μm, 0.025≤L / σ≤0.1, 0.18≤S / σ≤1.2, and 1≤w2-w1≤6. It can alleviate the lithium plating problem of the negative electrode sheet 1 on the basis of reducing the internal resistance of the battery and improving the cycle life of the battery, and is beneficial to the lithium insertion and deinsertion process at the edges of the positive and negative electrodes in the battery cell, so that the lithium ions are more evenly distributed in the electrolyte near the edge, inhibiting the generation of lithium plating at the edge of the negative electrode, and taking into account the improvement of the energy density and cycle life of the battery.
[0048] Specifically, the concave portion 13 may be in the shape of a hole or a groove, and preferably the concave portion 13 is a linear groove (such as a laser-etched groove), that is, the projection of the concave portion 13 on the negative electrode current collector 11 is a strip (such as Figure 2 As shown), specifically it can be a rectangle (as Figure 2 as shown) or other regular or irregular shapes.
[0049] Continue to refer Figure 1 Each recess 13 on the surface of the negative electrode active layer 12 is a linear groove, and its projection on the negative electrode current collector 11 is basically a rectangle. The length directions (extension directions) of these recesses 13 are basically parallel to each other, specifically parallel to the second direction y, and the width directions of these recesses 13 are basically parallel, basically parallel to the first direction x.
[0050] like Figure 2 As shown, the concave portion 13 can be a complete continuous groove, that is, a continuous groove is formed by continuously drilling holes on the surface of the negative electrode active layer 12 along the extension direction of the preset linear groove using a laser.
[0051] Specifically, if Figure 1 and Figure 2 As shown, the second direction y, the length direction of the recess 13, the width direction of the negative electrode active layer 12, the width direction of the negative electrode current collector 11, and the width direction of the negative electrode sheet 1 are basically parallel to each other, and the first direction x, the width direction of the recess 13, the length direction of the negative electrode active layer 12, the length direction of the negative electrode current collector 11, and the length direction of the negative electrode sheet 1 are basically parallel to each other.
[0052] In addition, if Figure 2As shown, the recess 13 extends from the surface of the negative electrode active layer 12 to the interior of the negative electrode active layer 12, and the depth direction of the recess 13 can be basically parallel to the third direction z. The third direction z, the thickness direction of the negative electrode active layer 12, the thickness direction of the negative electrode current collector 11, and the thickness direction of the negative electrode sheet 1 are parallel to each other.
[0053] In general, if Figure 2 As shown, the depth of the recess 13 is less than the thickness of the negative electrode active layer 12 , that is, the recess 13 does not penetrate the negative electrode active layer 12 in the thickness direction of the negative electrode active layer 12 , that is, the negative electrode active layer 12 exists between the recess 13 and the negative electrode current collector 11 .
[0054] In an embodiment of the present invention, a negative electrode active layer 12 may be provided on one surface of the negative electrode current collector 11, or a negative electrode active layer 12 may be provided on both the front and back surfaces of the negative electrode current collector 11 (the front and back surfaces of the negative electrode current collector 11). When a negative electrode active layer 12 is provided on both the front and back surfaces of the negative electrode current collector 11, the above-mentioned recess 13 may be provided on the negative electrode active layer 12 on both sides.
[0055] Specifically, the negative electrode current collector 11 may include copper foil.
[0056] In some embodiments, 15000≤σ*h≤51000, preferably, 23000≤σ*h≤51000, where h is the depth of the concave portion 13 in μm; σ is in kgf / cm 2 In this way, the separator 3 is more conducive to generating a binding force on the negative electrode sheet 1, effectively preventing the displacement and extension of the negative electrode active layer 12 due to factors such as stress, and can also restrain the material particles around the recessed portion 13 in the negative electrode active layer 12 through the separator 3, further improving the stability of the negative electrode sheet 1 and the structural stability of the battery cell formed by the positive electrode sheet 2, the separator 3 and the negative electrode sheet 1, further taking into account the reduction of the battery cycle expansion rate and internal resistance, and improving the battery's energy density and cycle life. Specifically, relatively speaking, the smaller the depth of the recess 13, the more conducive it is to retaining more of the negative electrode active layer 12, thereby facilitating a higher energy density for the negative electrode sheet. However, when the depth h of the recess 13 is small, the expansion space it provides for the silicon-carbon material is relatively small, resulting in a relatively large expansion of the negative electrode sheet. Therefore, a separator with greater tensile strength is required to restrain the expansion of the silicon-carbon material while avoiding the risk of the separator being punctured. Therefore, by synergistically regulating the depth h of the recess 13 and the tensile strength σ of the separator to meet the requirement of 15000≤σ*h≤51000, it is possible to further balance reducing the battery's cycle expansion rate and internal resistance, while improving the battery's energy density and cycle life. Furthermore, a requirement of 23000≤σ*h≤51000 can further improve the battery's energy density and cycle life.
[0057] According to the inventor's research, the surface of the negative electrode sheet 1 is formed with a recess 13 by laser etching or other methods (for example, parallel linear scratches are left after laser etching), which will affect the strength of the negative electrode sheet 1 to a certain extent. At the same time, in the preparation process of the negative electrode sheet 1, after the negative electrode sheet 1 is rolled, there is a strong stress between the material particles in the negative electrode active layer 12, which makes the material in the negative electrode active layer 12 tend to rebound outward, especially the material particles around the recess 13 are more likely to move toward the recess 13 due to stress extrusion, reducing the stability of the negative electrode active layer 12, and causing powder loss, wrinkling of the electrode sheet and other phenomena in the subsequent operation of the battery, affecting the life and electrochemical performance of the battery. By collaboratively controlling the ash content a of the negative electrode active layer to be 2% to 50% and the average silicon-carbon material content to be 1%. A particle size D of 1 to 15 μm, along with the conditions of 0.025 ≤ L / σ ≤ 0.1, 0.18 ≤ S / σ ≤ 1.2, and 1 ≤ w2 - w1 ≤ 6, can effectively alleviate these issues. Furthermore, according to further research by the inventors, by further synergistically regulating the depth h of the recess 13 and the tensile strength σ of the separator 3 to satisfy the requirement of 15000 ≤ σ*h ≤ 51000, the separator 3's binding force on the negative electrode sheet 1 can be further enhanced, further stabilizing the relative position of the separator 3 and the negative electrode active layer 12. This allows the material particles surrounding the recess 13 on the surface of the negative electrode active layer 12 to be more effectively bound by the separator 3, preventing powder shedding and wrinkling of the negative electrode sheet 1. This further reduces the battery's cycle expansion rate and internal resistance, improving battery performance such as energy density and cycle life. In particular, satisfying the requirement of 23000 ≤ σ*h ≤ 51000 can further improve battery performance such as energy density and cycle life.
[0058] Illustratively, σ*h may be 15000, 18000, 20000, 22000, 23000, 23800, 25000, 30000, 33000, 35000, 37000, 40000, 44000, 48000, 50000, 51000, or a range consisting of any two thereof.
[0059] In some embodiments, the tensile strength σ of the diaphragm 3 is 1350-3000 kgf / cm 2 , for example 1350kgf / cm 2 、1500kgf / cm 2 、1800kgf / cm 2 , 2000kgf / cm 2 、2300kgf / cm 2 、2500kgf / cm 2 、2800kgf / cm 2 、3000kgf / cm 2Or a range composed of any two of them, so that the diaphragm 3 has more suitable properties such as strength, which is beneficial to ion transmission, while maintaining a high strength of the diaphragm 3, improving its binding effect on the negative electrode active layer 12, and improving the overall structural stability of the battery cell formed by the positive electrode sheet 2, the diaphragm 3 and the negative electrode sheet 1, taking into account reducing the battery cycle expansion rate and internal resistance, and improving the battery's energy density and cycle life and other performance.
[0060] In the embodiment of the present invention, one side surface of the diaphragm 3 is bonded to the positive electrode sheet 2, and the other side surface of the diaphragm 3 is bonded to the negative electrode sheet 1. The positive electrode sheet 2 and the negative electrode sheet 1 are constrained by the diaphragm 3 to avoid problems such as the falling off (dropping) of the positive and negative electrode materials. At the same time, the structural stability and other performance of the battery cell formed by the positive electrode sheet 2, the diaphragm 3 and the negative electrode sheet 1 can be improved, while taking into account the reduction of the battery cycle expansion rate and internal resistance, and improving the battery's energy density and cycle life and other performance.
[0061] Generally, a battery includes a cell, which includes the above-mentioned negative electrode sheet 1, positive electrode sheet 2, and a separator 3 located between the positive electrode sheet 2 and the negative electrode sheet 1. The separator 3 is separated between the positive electrode sheet 2 and the negative electrode sheet 1 to prevent the positive electrode sheet 2 and the negative electrode sheet 1 from contacting and short-circuiting.
[0062] In a specific implementation, the positive electrode sheet 2 , the separator 3 and the negative electrode sheet 1 may be placed in sequence and then hot-pressed to form a battery cell.
[0063] Specifically, if Figure 4 As shown, the battery cell can be a wound battery cell (wound core), that is, the positive electrode sheet 2, the separator 3, and the negative electrode sheet 1 each have a wound structure. The positive electrode sheet 2 includes a plurality of first straight portions 110 and a first bent portion 120 connected between two adjacent first straight portions 110. The number of first bent portions 120 is generally at least one, and may be multiple. The positive electrode sheet 2 is bent through the first bent portion 120 to form a wound structure. The negative electrode sheet 1 includes a plurality of second straight portions 210 and a second bent portion 220 connected between two adjacent second straight portions 210. The number of second bent portions 220 is generally at least one, and may be multiple. The negative electrode sheet 1 is bent through the second bent portion 220 to form a wound structure.
[0064] In specific implementation, the positive electrode sheet 2, the separator 3 and the negative electrode sheet 1 can be placed in sequence, the formed laminated structure can be wound, and then hot pressed to hot press the positive electrode sheet 2, the separator 3 and the negative electrode sheet 1 into one to form a wound battery cell.
[0065] Specifically, if Figure 3As shown, the diaphragm 3 includes a base film 31 and a functional coating provided on the front and back surfaces of the base film 31. The functional coating may include a glue layer. The diaphragm 3 is bonded to the positive and negative electrode sheets 1 through the glue layer on its surface. That is, the side of the base film 31 facing the positive electrode sheet 2 and the side facing the negative electrode sheet 1 are respectively provided with a glue layer (hereinafter, the glue layer located on the side of the base film 31 facing the negative electrode sheet 1 is referred to as the first glue layer 33, and the glue layer located on the side of the base film 31 facing the positive electrode sheet 2 is referred to as the second glue layer 34), so that one side of the diaphragm 3 is bonded to the negative electrode sheet 1 through the first glue layer 33, and the other side is bonded to the positive electrode sheet 2 through the second glue layer 34.
[0066] In the embodiment of the present invention, the adhesive layer can be formed of conventional adhesive materials in the art. For example, the adhesive layer includes PVDF, and the first adhesive layer 33 and the second adhesive layer 34 can be PVDF layers formed of PVDF respectively.
[0067] In addition, the diaphragm may further include a ceramic layer 32 located on at least one side of the base film. The provision of the ceramic layer 32 in the diaphragm 3 improves heat dissipation, further reduces the battery's cycle expansion rate, and improves battery cycle life and other performance.
[0068] Specifically, if Figure 3 As shown, a ceramic layer 32 may be further provided between the base film 31 and the adhesive layer. The ceramic layer 32 may be provided on at least one side surface of the base film 31. For example, the ceramic layer 32 may be provided on the side surface of the base film 31 facing the positive electrode sheet 2, or on the side surface of the base film 31 facing the negative electrode sheet 1, or the side surface of the base film 31 facing the positive electrode sheet 2 and the side surface facing the negative electrode sheet 1 may be provided with a ceramic layer 32 respectively.
[0069] In some embodiments, as Figure 3 As shown, the ceramic layer 32 is located between the base film 31 and the second coating layer 34, that is, the diaphragm 3 includes the base film 31, the first coating layer 33 located on the side of the base film 31 facing the negative electrode sheet 1, the ceramic layer 32 located on the side of the base film 31 facing the positive electrode sheet 2, and the second coating layer 34 located on the side of the ceramic layer 32 facing the positive electrode sheet 2, which is beneficial to reducing the cycle expansion rate of the battery and improving the cycle life and other performance of the battery.
[0070] Specifically, the thickness H of the ceramic layer 32 is 32 The thickness may be 0.5 to 5 μm, for example, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, or a range consisting of any two thereof.
[0071] Specifically, the ceramic layer 32 includes a ceramic material, which may include one or more of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, and titanium oxide. For example, the ceramic layer 32 may be an aluminum oxide layer or a boehmite layer. The embodiment of the present invention can form the ceramic layer 32 by conventional methods in the art, for example, by coating the ceramic material on the surface of the base film 31 by a coating method to form the ceramic layer 32.
[0072] In specific implementation, the production process of the base film 31, the material of the base film 31 and other conditions can be adjusted to control the tensile strength and other characteristics of the diaphragm 3. These are conventional operations in this field and will not be repeated here.
[0073] For example, the base film 31 can be a conventional membrane material in this field, such as a polypropylene (PP) membrane (PP film), a polyethylene (PE) membrane (PE film), a polypropylene / polyethylene (PP / PE) double-layer composite membrane, a polyimide electrospun membrane (PI), a polypropylene / polyethylene / polypropylene (PP / PE / PP) three-layer composite membrane, or a cellulose non-woven membrane.
[0074] In some embodiments, 0.00014 ≤ k / S ≤ 0.0005, where k / S is, for example, 0.00014, 0.00015, 0.00017, 0.0002, 0.00024, 0.00028, 0.0003, 0.00032, 0.00035, 0.00038, 0.0004, 0.00045, 0.0005, or a range consisting of any two thereof, where k is the porosity of the base film 31 and S is the spacing of the recesses 13, both measured in μm. This helps to further balance reducing the battery expansion rate with improving the battery's cycle life.
[0075] In some embodiments, 0.15 ≤ A / S ≤ 0.4, where A / S is, for example, 0.15, 0.2, 0.25, 0.3, 0.33, 0.35, 0.38, 0.4, or a range consisting of any two thereof, where A is the pore size of the base film 31 in nm, and S is the spacing between the recesses 13 in μm. This helps to further balance reducing the battery expansion rate and improving the battery cycle life.
[0076] According to the inventor's research, the concave portion 13 on the surface of the negative electrode active layer 12 can not only provide expansion space and release stress for negative electrode active materials such as silicon-carbon materials, but also provide a channel for the electrolyte to infiltrate the negative electrode active material particles. The electrolyte flowing into the concave portion 13 can more quickly contact the negative electrode active material in the lower layer of the negative electrode active layer 12 (close to the negative electrode current collector 11), thereby improving the ion migration ability. At the same time, the porosity and pore size of the diaphragm 3 and other characteristics will also affect the electrolyte infiltration and ion diffusion. Specifically, the porosity and / or pore size of the diaphragm 3 will affect the liquid retention of the battery cell (that is, the amount of electrolyte retained in the battery cell) and affect the ion transmission rate. (The larger the porosity and / or pore size of the diaphragm 3, the more conducive it is for the electrolyte to infiltrate the battery cell and increase the liquid retention of the battery cell). Therefore, when the porosity k and / or pore size A of the base membrane are relatively large, a larger recess 13 spacing S can be adapted. In this way, the number of recesses 13 is relatively small, and more negative electrode active materials can be retained, so that the negative electrode sheet has a higher energy density. At the same time, based on the larger porosity k and / or pore size A of the diaphragm, it can take into account the maintenance of electrolyte infiltration of the battery cell and increase the electrolyte retention of the battery cell, thereby facilitating the transmission of lithium ions, reducing ionic resistivity, reducing cyclic polarization (electrochemical polarization), and improving the cycle life of the battery and other performance. Therefore, on the basis of satisfying the ash content a of the negative electrode active layer of 2% to 50%, the average particle size of the silicon-carbon material of 1 to 15 μm, 0.025≤L / σ≤0.1, 0.18≤S / σ≤1.2, and 1≤w2-w1≤6, while suppressing the expansion of the negative electrode sheet, by further synergistically regulating the spacing S of the recesses 13 on the surface of the negative electrode active layer 12 and the porosity k and / or pore size A of the diaphragm 3, so as to satisfy 0.0014≤k / S≤0.0005 and / or 0.15≤A / S≤0.4, the negative electrode sheet 1 and the diaphragm 3 are more compatible. Based on the synergistic cooperation between the two, the wettability of the electrolyte to the battery cell, the liquid retention capacity and ion transmission capacity of the battery cell are further improved, the ionic resistivity is reduced, the cyclic polarization (electrochemical polarization) is reduced, and the cycle life and other performance of the battery are improved.
[0077] In some embodiments, 18 ≤ k*L ≤ 57, where k*L is, for example, 18, 20, 25, 30, 34, 38, 40, 45, 50, 54, 57, or any two thereof, where k is the porosity of the base film 31 and L is the width of the recess 13, both in μm. This helps to further balance reducing the battery's expansion rate with improving its cycle life.
[0078] In some embodiments, 19000≤A*L≤60000, where A*L is, for example, 19000, 19800, 20000, 24000, 28000, 30000, 33000, 36000, 40000, 45000, 50000, 55000, 60000, or a range consisting of any two thereof, where A is the pore diameter of the base film 31 in nm, and L is the width of the recess 13 in μm. This helps to further balance reducing the battery expansion rate and improving the battery cycle life.
[0079] According to the inventor's research, as mentioned above, the concave portion 13 on the surface of the negative electrode active layer 12 can not only provide expansion space and release stress for negative electrode active materials such as silicon carbon materials, but also provide a channel for the electrolyte to infiltrate the negative electrode active material particles. The electrolyte flowing into the concave portion 13 can more quickly contact the negative electrode active material in the lower layer of the negative electrode active layer 12 (close to the negative electrode current collector 11), thereby improving the ion migration ability. At the same time, the porosity and pore size of the diaphragm 3 and other characteristics will also affect the electrolyte infiltration and ion diffusion. Specifically, the porosity and / or pore size of the diaphragm 3 will affect the liquid retention of the battery cell (i.e., the amount of electrolyte retained in the battery cell) and affect the ion transmission speed. rate (the larger the porosity and / or pore size of the diaphragm 3, the more conducive it is for the electrolyte to infiltrate the battery cell and increase the liquid retention of the battery cell). Therefore, when the porosity k and / or pore size A of the base membrane are relatively large, a smaller width L of the recess 13 can be adapted. In this way, the width L of the recess 13 is relatively small, which can retain more negative electrode active materials and make the negative electrode sheet have a higher energy density. At the same time, based on the larger porosity k and / or pore size A of the diaphragm, it can take into account the maintenance of the electrolyte infiltration of the battery cell and increase the liquid retention of the electrolyte by the battery cell, thereby facilitating the transmission of lithium ions, reducing ionic resistivity, reducing cyclic polarization (electrochemical polarization), and improving the cycle life and other performance of the battery. Therefore, on the basis of satisfying the ash content a of the negative electrode active layer of 2% to 50%, the average particle size of the silicon-carbon material of 1 to 15 μm, 0.025≤L / σ≤0.1, 0.18≤S / σ≤1.2, and 1≤w2-w1≤6, while suppressing the expansion of the negative electrode sheet, by further synergistically regulating the width L of the recess 13 on the surface of the negative electrode active layer 12 and the porosity k and / or pore size A of the diaphragm 3, so as to satisfy 18≤k*L≤57 and / or 19000≤A*L≤60000, the negative electrode sheet 1 and the diaphragm 3 are more compatible. Based on the synergistic cooperation between the two, while suppressing the expansion of the negative electrode sheet, the wettability of the electrolyte to the battery cell, the liquid retention capacity and ion transmission capacity of the battery cell are further improved, the ionic resistivity is reduced, the cyclic polarization (electrochemical polarization) is reduced, and the cycle life and other performance of the battery are improved.
[0080] In some embodiments, the porosity k of the base film 31 can be 20% to 60%, for example, 20%, 30%, 40%, 50%, 60% or a range composed of any two of them, which is beneficial to improving the electrolyte wettability and ion transmission ability of the battery cell, and further improving the battery's cycle life and other performance.
[0081] In some embodiments, the pore size A of the base membrane 31 can be 50 to 550 nm, for example, 50 nm, 100 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm or a range consisting of any two of them, which is beneficial to improving the electrolyte wettability and ion transmission ability of the battery cell, and further improving the battery's cycle life and other performance.
[0082] In some embodiments, 13000≤L*B≤34000, B is the air permeability of the diaphragm 3, measured in s; L is the width of the recess 13, measured in μm, and L*B is, for example, 13000, 13500, 13560, 15000, 17000, 20000, 20340, 25000, 30000, 33000, 33900, 34000 or a range consisting of any two of them, which is beneficial to further take into account both reducing the expansion rate of the battery and improving the cycle life of the battery.
[0083] According to the inventor's research, the permeability S of the diaphragm 3 represents the ability of gas to pass through the diaphragm 3 material per unit time, which to a certain extent reflects the transmission ability of the diaphragm 3 to active ions such as lithium ions. At the same time, the permeability of the diaphragm 3 will also affect the wettability of the electrolyte to the battery cell. By synergistically regulating the width L of the recess 13 and the permeability B of the diaphragm 3, so as to satisfy 13000≤L*B≤34000, it is beneficial to form a better electrolyte infiltration channel in the battery cell, and at the same time it is beneficial to ion transmission, further improving the wettability of the electrolyte to the battery cell, the liquid retention capacity and ion transmission capacity of the battery cell, reducing the ionic resistivity, reducing cyclic polarization (electrochemical polarization), and improving the cycle life and other performance of the battery.
[0084] In some embodiments, the air permeability B of the diaphragm 3 can be 100 to 350 sec / 100cc, for example, 100 sec / 100cc, 130 sec / 100cc, 150 sec / 100cc, 180 sec / 100cc, 200 sec / 100cc, 230 sec / 100cc, 250 sec / 100cc, 280 sec / 100cc, 300 sec / 100cc, 330 sec / 100cc, 350 sec / 100cc or a range consisting of any two of them, which is beneficial to further improve the wettability of the electrolyte to the battery cell, reduce the ion transfer resistance, and improve the cycle life of the battery and other performance.
[0085] like Figure 5 As shown, the width w2 of the separator 3 is greater than the width w1 of the negative electrode sheet 1, so that the separator 3 covers the negative electrode sheet 1, which is beneficial to prevent the positive and negative electrodes from short-circuiting and improve the safety and other performance of the battery.
[0086] Specifically, if Figure 5 As shown, the width w2 of the separator 3 is the width of the separator 3 in the second direction y, and the width w1 of the negative electrode sheet 1 is the width of the negative electrode sheet 1 in the second direction y, that is, the width direction of the separator 3, the width direction of the negative electrode sheet 1 and the second direction y are parallel to each other.
[0087] It should be noted that when the battery cell is a wound battery cell (the positive electrode sheet 2, the separator 3 and the negative electrode sheet 1 are wound to form a wound structure), the width w2 of the separator 3 mentioned above refers to the width before the separator 3 is wound, and the width w1 of the negative electrode sheet 1 refers to the width before the negative electrode sheet is wound.
[0088] In some embodiments, 250≤S / C≤1300, where S / C is, for example, 250, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, or a range consisting of any two thereof; C is the difference between the width w2 of the separator 3 and the width w1 of the negative electrode sheet 1 (C = w2 - w1, i.e., 250≤S / (w2 - w1)≤1300), measured in mm; and S is the spacing of the recesses 13, measured in μm, which is beneficial to further take into account the improvement of battery safety, cycle life and other performance.
[0089] According to the inventors' further research, when the spacing between recesses 13 is relatively large, the number of recesses 13 on the surface of the negative electrode active layer 12 is relatively small, resulting in relatively severe expansion of the negative electrode active layer 12 and a relatively large tendency to extend. Therefore, a larger separator is required to further avoid the risk of positive-negative electrode short circuit caused by the relatively large extension of the negative electrode sheet, thereby further improving battery safety and cycle life. Therefore, while synergistically controlling the ash content a of the negative electrode active layer to be 2% to 50%, the average particle size of the silicon-carbon material to be 1 to 15 μm, 0.025 ≤ L / σ ≤ 0.1, 0.18 ≤ S / σ ≤ 1.2, and 1 ≤ w2 - w1 ≤ 6, the spacing S between the recesses 13 and the difference C between the width w2 of the separator 3 and the width w1 of the negative electrode sheet 1 are further coordinated to meet the requirements of 250 ≤ S / C ≤ 1300, thereby further improving battery safety and cycle life.
[0090] In general, the negative electrode active layer 12 includes a negative electrode active material, which includes a silicon-carbon material, or a silicon-carbon material and other negative electrode materials. Other negative electrode materials include, for example, carbon-based materials, silicon-oxygen materials, nano-silicon particles and other negative electrode active materials. For example, the negative electrode active material may also include carbon-based materials and silicon-carbon materials. Among them, the carbon-based material may include one or more of graphite, mesophase carbon microbeads, soft carbon, and hard carbon. The graphite may include artificial graphite and / or natural graphite (that is, the carbon-based material may include at least one of artificial graphite and natural graphite).
[0091] In some embodiments, the negative electrode active material in the negative electrode active layer 12 includes carbon-based materials and silicon-carbon materials, and specifically may include graphite and silicon-carbon materials.
[0092] In some embodiments, the ratio of the mass of the silicon-carbon material to the mass of the negative electrode active material (i.e., the silicon doping amount of the negative electrode active layer 12) can be 2% to 50%, for example, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range composed of any two of them. This is beneficial for increasing the capacity of the negative electrode sheet 1 while maintaining a low expansion rate of the negative electrode sheet 1, further reducing the battery cycle expansion rate and internal resistance, reducing the negative electrode lithium plating phenomenon, and improving the energy density and cycle life of the battery.
[0093] In some embodiments, the proportion of silicon in the silicon-carbon material may be 20 wt% to 60 wt%, for example, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt% or any two thereof.
[0094] In the embodiment of the present invention, the proportion of silicon element in the silicon-carbon material can be measured by conventional methods in the art, and specifically can be obtained by testing and analyzing silicon-carbon particles through SEM-EDS.
[0095] In addition, the negative electrode active layer 12 also includes materials such as a conductive agent, a binder and a thickener. Based on the total mass of the negative electrode active layer 12, the mass fraction of the negative electrode active material can be 70% to 99%, for example, 70%, 75%, 80%, 85%, 90%, 95%, 99% or a range consisting of any two thereof, the mass fraction of the conductive agent can be 0.3% to 12%, for example, 0.3%, 0.5%, 1%, 3%, 5%, 8%, 10%, 12% or a range consisting of any two thereof, and the mass fraction of the binder can be 0.3% to 12%, for example, 0.3%, 0.5%, 1%, 3%, 5%, 8%, 10%, 12% or a range consisting of any two thereof. The mass fraction of the binder can be 0% to 15%, for example, 0, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 7%, 9%, 10%, 12%, 15% or a range consisting of any two of them, and the mass fraction of the thickener can be 0% to 3%, for example, 0, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or a range consisting of any two of them, but is not limited to this.
[0096] Specifically, the thickener, conductive agent and binder in the negative electrode active layer 12 can be conventional materials in the art. For example, the thickener can include a carboxymethyl cellulose (CMC) thickener, for example, carboxymethyl cellulose salts, such as carboxymethyl cellulose lithium (CMC-Li), CMC-Na, etc.; the binder in the negative electrode coating can include one or more of styrene-butadiene rubber (SBR), polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate; the conductive agent in the negative electrode active layer 12 can include one or more of carbon nanotubes (CNTs), carbon black (SP), acetylene black, and graphene.
[0097] In addition, if Figure 3 As shown, the positive electrode sheet 2 includes a positive electrode current collector 21 and a positive electrode active layer 22 located on the surface of the positive electrode current collector 21 . Specifically, the positive electrode active layer 22 may be provided on both the front and back surfaces of the positive electrode current collector 21 .
[0098] In the embodiment of the present invention, the positive electrode current collector 21 may include a conventional negative electrode current collector 11 in the art, such as aluminum foil, and is not particularly limited thereto.
[0099] Specifically, the positive electrode active layer 22 may include a positive electrode active material, a conductive agent and a binder. The positive electrode active material may include conventional positive electrode active materials in the art, for example, a positive electrode lithium-containing active material, for example, lithium cobaltate, lithium manganese oxide, lithium nickel oxide, a ternary material, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, and at least one of lithium-rich manganese-based materials. The ternary material may include lithium nickel cobalt manganese oxide and / or lithium nickel cobalt aluminum oxide, etc.
[0100] In addition, based on the total mass of the positive electrode active layer 22, the mass fraction of the positive electrode active material can be 70% to 99%, for example, 70%, 75%, 80%, 85%, 90%, 95%, 99% or a range consisting of any two thereof, the mass fraction of the conductive agent can be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 7%, 9%, 10%, 12%, 15% or a range consisting of any two thereof, and the mass fraction of the binder can be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 7%, 9%, 10%, 12%, 15% or a range consisting of any two thereof, but is not limited to this.
[0101] In an embodiment of the present invention, the binder in the positive electrode active layer 22 can be a conventional binding material in the art, for example, one or more of polyvinylidene fluoride (PVDF), a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, carboxymethyl cellulose sodium (CMC), polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, polyhexafluoropropylene and styrene-butadiene rubber (SBR).
[0102] In the embodiment of the present invention, the conductive agent in the positive electrode active layer 22 may be a conventional conductive material in the art, for example, one or more of carbon nanotubes (CNTs), carbon black (SP), acetylene black, and graphene.
[0103] In an embodiment of the present invention, the positive electrode sheet 2 can be prepared by conventional methods in the field such as a coating method. For example, the preparation process of the positive electrode sheet 2 may include: placing materials such as a positive electrode active material, a conductive agent and a binder in a solvent to prepare a positive electrode slurry, and the solvent used includes, for example, N-methylpyrrolidone (NMP), and then applying the positive electrode slurry to the surface of the positive electrode collector 21. After drying, rolling and other processes, a positive electrode active material layer is formed on the surface of the positive electrode collector 21. Subsequently, after conventional processes such as cutting, welding the positive electrode tab 200, and attaching adhesive tape on the surface of the positive electrode tab 200, a positive electrode sheet 2 of a preset size and shape is obtained.
[0104] In an embodiment of the present invention, a negative electrode active layer 12 can be formed on the surface of a negative electrode current collector 11 by a conventional method in the art, such as a coating method, and then the surface of the negative electrode active layer 12 can be perforated by laser to produce a negative electrode sheet 1. For example, the process of producing the negative electrode sheet 1 may include placing materials such as a negative electrode active material, a conductive agent, and a binder in a solvent, such as water, to form a negative electrode slurry. The solvent used may then be applied to the surface of the negative electrode current collector 11. After drying (baking) and rolling, the negative electrode active layer 12 is formed on the surface of the negative electrode current collector 11. Conventional processes such as cutting, welding the negative electrode tab 100, and attaching adhesive tape to the surface of the negative electrode tab 100 are then performed. Finally, a recess 13 is formed in a predetermined area on the surface of the negative electrode active layer 12 by laser etching, etc., to produce the negative electrode sheet 1. In an embodiment of the present invention, conventional laser equipment in the art is used for laser etching, and this is not particularly limited.
[0105] In an embodiment of the present invention, the battery further includes a shell for encapsulating the battery cell, and the shell may include a soft packaging film (i.e., the battery is a soft packaging battery), which may be a soft packaging film formed by conventional soft packaging materials in the art. For example, the shell includes an aluminum-plastic film, but is not limited thereto.
[0106] In addition, if Figure 4 As shown, the battery also includes tabs connected to the battery cell, and the tabs include a negative tab 100 connected to the negative current collector 11, and a positive tab 200 connected to the positive current collector 21. The negative tab 100 and the positive tab 200 both extend out of the shell to connect the battery and the electronic product using the battery.
[0107] In an embodiment of the present invention, the battery further includes an electrolyte, which is injected into the shell to soak the battery cell.
[0108] The embodiments of the present invention may adopt conventional electrolytes in the art. For example, the electrolyte includes a solvent and a solute. The electrolyte may specifically be a non-aqueous electrolyte, wherein the solvent may include an organic solvent, specifically a carbonate solvent, for example, one or more of ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC), and propyl propionate (PP); the solute may include a lithium salt, and the lithium salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), etc.
[0109] The electrolyte may also include additives, which may specifically include one or more of adiponitrile (ADN), 1,3,6-hexanetrionitrile (HTCN), succinonitrile, glycerol trinitrile, 1,4-dicyano-2-butene, ethylene glycol bis(propionitrile) ether, 1,3-propane sultone, 1,3-propylene sultone, fluoroethylene carbonate, and vinylene carbonate. The mass ratio of the additive to the electrolyte (i.e., the mass content of the additive in the electrolyte) may be 0.01 to 20 wt%.
[0110] In an embodiment of the present invention, the battery can be manufactured according to conventional methods in the field. For example, the positive electrode sheet 2, the separator 3, and the negative electrode sheet 1 are wound to form a core, and hot-pressed together, and then packaged in a shell. After baking, liquid injection (electrolyte is injected into the shell), formation, and secondary sealing, the battery is obtained. These steps / processes are all conventional operations in the field. The present invention does not impose any special restrictions on this and will not be repeated.
[0111] In an embodiment of the present invention, the width L, spacing S, and depth h of the recesses on the surface of the negative electrode active layer can be measured by an elemental analysis microscope. Specifically, a photograph of the surface of the negative electrode active layer with recesses distributed thereon can be taken at a magnification of 200 times to measure the width L of the recesses. The spacing S and depth h of the recesses can be tested at a magnification of 100 times.
[0112] In the embodiment of the present invention, the tensile strength σ of the diaphragm is the tensile strength of the diaphragm in a direction perpendicular to the length of the recess, that is, the tensile strength σ of the diaphragm is the tensile strength of the diaphragm in a direction parallel to the width direction. The testing process of the tensile strength σ of the diaphragm may specifically include: cutting the diaphragm into small strips with a size of 15 mm ± 0.2 mm in the transverse and longitudinal directions respectively to obtain a diaphragm sample; using a WD-D3 electronic universal testing machine with a 50 mm gap between the upper and lower clamps, clamping the two ends of the diaphragm sample in the clamps respectively, starting the test at a speed of 100 mm / min until the equipment stops testing, recording the tensile strength σ of the diaphragm sample, and performing the test three times according to this process (with an error of no more than 10%), and taking the average value, which is the tensile strength σ of the diaphragm.
[0113] In an embodiment of the present invention, after the diaphragm is disassembled from the battery, the functional coatings such as the adhesive layer on the diaphragm will generally adhere to the electrode, so the disassembled diaphragm is basically a base membrane. Therefore, after the diaphragm is disassembled from the battery, the porosity k, pore size A and other characteristics of the disassembled diaphragm can be directly tested. The measured porosity is the porosity k of the above-mentioned base membrane, and the measured pore size is the pore size A of the base membrane; alternatively, after obtaining the thickness of the diaphragm, the base membrane can be separated by other conventional methods in the field, and then its porosity k, pore size A and other characteristics can be tested.
[0114] Specifically, the testing process of the porosity k of the base film in the diaphragm may include: cutting the base film to obtain a base film sample with an area greater than 0.1 m2 or a weight greater than 3 g, measuring the thickness of the base film sample, and obtaining the measured thickness of the base film sample; after folding, the base film sample is placed in a sample cup, and a true density meter is used to test the true volume V0 of the base film sample, and the apparent volume V1 of the base film sample is calculated (V1 = measured base film sample thickness * base film length * base film width), then the base film porosity = (V1-V0) / V1.
[0115] In addition, the test process of the pore size A of the base film in the diaphragm may include: cutting the base film to obtain an area larger than 25 cm 2 Or for basement membrane samples weighing more than 3g, use a PMI pore size analyzer to test the pore size of the basement membrane sample, which is the pore size A of the basement membrane. Or cut the diaphragm and measure it through SEM observation.
[0116] In the embodiment of the present invention, the permeability B of the diaphragm represents the ability of gas to pass through the diaphragm material per unit time. After the diaphragm is disassembled from the battery, the permeability B of the diaphragm can be measured by the following process: cutting the diaphragm to obtain an area larger than 9cm 2 The membrane sample is tested for air permeability using an air permeability tester. The test is repeated three times and the average value is taken as the air permeability B of the membrane. The air permeability tester used can be Wang Yan's air permeability tester (model EG01-55-1MR).
[0117] In the embodiment of the present invention, the difference c between the width of the separator and the width of the negative electrode sheet can be measured by the following process: measuring the width E1 of the negative electrode sheet and the width E2 of the separator in the battery cell, and then C=E2-E1.
[0118] The present invention is further described below through specific examples. In the following examples and comparative examples, the silicon-carbon particles (silicon-carbon material) used include porous carbon and porous silicon present in the pores of the porous carbon, and the silicon content of the silicon-carbon particles is between 40 wt% and 45 wt%.
[0119] Example 1
[0120] 1. Preparation of positive electrode
[0121] Lithium cobalt oxide, conductive carbon black, carbon nanotubes, and PVDF were mixed uniformly in NMP at a mass ratio of 95:1:1.5:2.5 to prepare a positive electrode slurry;
[0122] The positive electrode slurry is coated on the front and back surfaces of the aluminum foil. After drying and rolling, the positive electrode active layer is formed on the front and back surfaces of the aluminum foil. Subsequently, the positive electrode tabs are cut and welded, and adhesive tape is pasted on the surface of the positive electrode tabs to produce the positive electrode sheet.
[0123] 2. Preparation of negative electrode sheet
[0124] Sodium carboxymethyl cellulose (CMC-Na) is dissolved in deionized water to prepare a gel, and then a negative electrode active material and conductive carbon black are mixed and added to the gel, and stirred evenly, and then SBR is added thereto, and stirred evenly to obtain a negative electrode slurry; wherein the negative electrode active material includes silicon carbon particles and artificial graphite (the mass ratio of silicon carbon particles to artificial graphite is about 7:93), and the mass ratio of the negative electrode active material, conductive carbon black, SBR, and CMC-Na is 96:0.5:2:1.5;
[0125] The negative electrode slurry is coated on the front and back surfaces of the copper foil, and then baked and rolled to form a negative electrode active layer on the front and back surfaces of the copper foil. Then, the negative electrode tabs are cut and welded, and adhesive tape is applied to the surface of the negative electrode tabs. Then, a laser is used to etch the surface of the negative electrode active layer on each side to form a concave portion (see the surface photo of the negative electrode sheet for details). Figure 2 ).
[0126] 3. Preparation of lithium-ion batteries
[0127] The positive electrode sheet and the negative electrode sheet are separated by a diaphragm, wound into a roll core, and hot-pressed together, and then encapsulated in an aluminum-plastic film shell. After baking, liquid injection, formation, and secondary sealing, a lithium-ion battery is produced.
[0128] The composition of the electrolyte is as follows: the mass ratio of ethylene carbonate (EC) to diethyl carbonate (DEC) is 3:7, and the concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L.
[0129] Among them, the diaphragm includes a base film (PE film), a first coating layer located on the side of the base film facing the negative electrode sheet, a ceramic layer (boehmite layer) located on the side of the base film facing the positive electrode sheet, and a second coating layer located on the side of the ceramic layer facing the positive electrode sheet. The thickness of the base film is 5μm, the thickness of the first coating layer is 1μm, the thickness of the second coating layer is 1μm, the first coating layer and the second coating layer are both oil-based PVDF layers, and the thickness of the ceramic layer is 2μm.
[0130] Examples 2 to 27, Comparative Examples 1 to 7: The difference from Example 1 is that the conditions such as the tensile strength σ of the diaphragm, the recess L, the recess spacing S, the recess depth h, the average particle size D of the silicon-carbon particles, the ash content a, the porosity K of the base membrane, the pore size A of the base membrane, the air permeability B of the diaphragm, the difference C between the width of the diaphragm and the width of the negative electrode sheet (i.e., w2-w1), L / σ, σ*h, k / S, A / S, k*L, A*L, L*B, S / (w2-w1) are different. See Tables 1 and 2 for details. Except for the differences shown in Tables 1 and 2, the other conditions are the same as those in Example 1.
[0131] The batteries of the embodiments and comparative examples were tested by the following process. The results are shown in Table 3.
[0132] (1) Battery 25°C cycle performance test: At 25°C, the lithium-ion battery was charged at 1C to the cut-off voltage, charged at a constant voltage to a cut-off current of 0.05C, and discharged at 1C to the lower limit voltage. The above charge and discharge steps were repeated 400 times (400 cycles (400T)). The battery capacity retention rate after 400T cycles at 25°C was measured. The results are shown in Table 3.
[0133] (2) 25°C Cycling Expansion Rate: Fully charge the lithium-ion battery before cycling, and measure the thickness B1 of the lithium-ion battery before cycling. After cycling 400 times according to the charge and discharge steps in (1), fully charge the lithium-ion battery, and measure the thickness B2 of the lithium-ion battery. The 25°C cycling 400T expansion rate of the lithium-ion battery = (B2-B1) / B1. The results are shown in Table 3.
[0134] (3) 25℃ cycle dissection: The lithium-ion battery that was cycled for 400T according to the charge and discharge steps in (1) was fully charged and dissected (disassembled) in a dry room to check whether the negative electrode had lithium and the location of lithium deposition. The results of the 25℃ cycle 400T dissection are shown in Table 3.
[0135] (4) Cyclic DC internal resistance: A lithium-ion battery that has been cycled for 400 T according to the charge and discharge steps in (1) is fully charged, discharged at 0.1C for 10 s, and the voltage V1 at the end of discharge is measured. It is then discharged at 1C for 150 s, and the voltage V2 at the end of discharge is measured. The DC internal resistance of the lithium-ion battery is measured to be (V1-V2) / (1C-0.1C).
[0136] (5) Battery volume energy density: The volume energy density of a lithium-ion battery is ED = E / V, where E is the discharge energy of the battery. The test method is as follows: charge the lithium-ion battery to the upper limit voltage at a current of 0.2C, then charge it at a constant voltage until the current drops to 0.02C, and then discharge it at a current of 0.2C to 3.0V. The discharged energy is E; V is the volume of the lithium-ion battery. The volume V of the lithium-ion battery is obtained by measuring the thickness, width and length of the lithium-ion battery and calculating the product of the three.
[0137] Table 1
[0138]
[0139] Table 2
[0140]
[0141]
[0142] Table 3
[0143]
[0144]
[0145] It can be seen from Table 1, Table 2 and Table 3 that, relative to Comparative Examples 1 to 7, Examples 1 to 27 control the ash content a of the negative electrode active layer within the range of 2% to 50%, the average particle size D of the silicon-carbon material within the range of 1 to 15 μm, and simultaneously control 1 ≤ w2 - w1 ≤ 6, 0.025 ≤ L / σ ≤ 0.1, and 0.18 ≤ S / σ ≤ 1.2, thereby being able to simultaneously reduce the DC internal resistance of the battery and improve the cycle life of the battery, while also maintaining a low expansion rate of the battery, alleviating the problem of lithium plating at the negative electrode, and maintaining a high energy density of the battery, especially Examples 1 to 8, Example 10, Example 12 to Example 19, and Example 20. 28 By further controlling at least one of the following conditions: 0.027≤L / σ≤0.07, 23000≤σ*h≤51000, 0.00014≤k / S≤0.0005, 0.15≤A / S≤0.4, 18≤k*L≤57, 19000≤A*L≤60000, 13000≤L*B≤34000, and 250≤S / (w2-w1)≤1300, it is beneficial to further balance the reduction of the DC internal resistance of the battery and the improvement of the cycle life of the battery, maintain a low expansion rate of the battery, alleviate lithium plating at the negative electrode, maintain a high energy density of the battery, and further improve the overall electrochemical performance of the battery.
[0146] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lithium-ion secondary battery, characterized in that: The device comprises a positive electrode sheet, a negative electrode sheet, and a separator located between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode active layer, the negative electrode active layer comprises a negative electrode active material, the negative electrode active material comprises a silicon-carbon material, and a concave portion is provided on the surface of the negative electrode active layer; The silicon-carbon material includes porous carbon and silicon present in the pores of the porous carbon; The ash content a of the negative electrode active layer is 2% to 50%; The average particle size of the silicon-carbon material is 1 to 15 μm; The lithium-ion secondary battery satisfies: 1≤w2-w1≤6; 0.025≤L / σ≤0.1; 0.18≤S / σ≤1.2; Wherein, w1 is the width of the negative electrode sheet, in mm; w2 is the width of the separator, in mm; L is the width of the recess, in μm; S is the spacing of the recesses, in μm; σ is the tensile strength of the separator, in kgf / cm 2 count.
2. The lithium-ion secondary battery according to claim 1, wherein 15000≤σ*h≤51000, the unit of σ is kgf / cm 2 h is the depth of the concave portion, in μm; Preferably, 23000≤σ*h≤51000.
3. The lithium-ion secondary battery according to claim 1, wherein The diaphragm includes a base film and a ceramic layer located on at least one side of the base film.
4. The lithium-ion secondary battery according to claim 3, wherein 0.00014≤k / S≤0.0005; and / or, 0.15≤A / S≤0.4; and / or, 18≤k*L≤57; and / or, 19000≤A*L≤60000; Wherein, k is the porosity of the basement membrane; A is the pore size of the basement membrane, in nm; L is in μm; S is in μm; and / or, the porosity k of the base film is 20% to 60%; And / or, the pore size A of the basement membrane is 50 to 550 nm.
5. The lithium-ion secondary battery according to claim 3, wherein The ceramic layer is located on a side of the base film facing the positive electrode sheet.
6. The lithium-ion secondary battery according to claim 1, wherein 13000≤L*B≤34000, where L is measured in μm; B is the air permeability of the diaphragm, measured in sec / 100cc; Preferably, the air permeability B of the separator is 100 to 350 sec / 100cc.
7. The lithium-ion secondary battery according to claim 1, wherein 250≤S / (w2-w1)≤1300, the units of w1 and w2 are mm; the unit of S is μm.
8. The lithium-ion secondary battery according to claim 1, wherein 0.027≤L / σ≤0.
07.
9. The lithium-ion secondary battery according to any one of claims 1 to 8, characterized in that: The width L of the concave portion is 60 to 150 μm; and / or, the spacing S of the recesses is 800 to 2800 μm; and / or, the depth h of the recess is 5 to 30 μm; And / or, the tensile strength σ of the separator is 1350 to 3000 kgf / cm 2 .
10. The lithium-ion secondary battery according to any one of claims 1 to 8, characterized in that: The negative electrode active material includes a carbon-based material and the silicon-carbon material; Preferably, the carbon-based material comprises at least one of artificial graphite and natural graphite; Preferably, the silicon element in the silicon-carbon material accounts for 20 wt% to 60 wt%.